2019
DOI: 10.1111/jicd.12401
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory potential of a carvedilol gel in the pulpal tissue of rats after dental bleaching: A histopathological evaluation

Abstract: Aim Carvedilol is an antioxidant that decreases inflammation in periodontitis. The hydrogen peroxide (H2O2) of bleaching gel causes inflammation and necrosis of the dental pulp. In the present study, we evaluated the anti‐inflammatory potential of carvedilol in the pulp of rats after bleaching. Methods The right upper molars of rats received 35% H2O2 (1× 30 minutes), and the left upper molars were used as the control. Half of the rats received carvedilol gel (1× 10 minutes), forming the following groups: bleac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The results also demonstrated that bleaching with hydrogen peroxide or carbamide peroxide promoted a statistically significant decrease in the microhardness of the enamel samples studied (p < 0.05), for which reason the null hypothesis of the study was rejected. Some studies have reported a loss of calcium [9,11,[25][26][27], alterations in surface morphology [28,29], changed in chemical composition [30], and a decrease in enamel microhardness [25,28] in teeth subjected to bleaching procedures, the last of which was observed in the present study. These findings could be explained by daily exposure to bleaching substances with pH values ranging between 5.2 and 5.8, which could initiate a descaling process involving the loss of minerals such as calcium [31].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The results also demonstrated that bleaching with hydrogen peroxide or carbamide peroxide promoted a statistically significant decrease in the microhardness of the enamel samples studied (p < 0.05), for which reason the null hypothesis of the study was rejected. Some studies have reported a loss of calcium [9,11,[25][26][27], alterations in surface morphology [28,29], changed in chemical composition [30], and a decrease in enamel microhardness [25,28] in teeth subjected to bleaching procedures, the last of which was observed in the present study. These findings could be explained by daily exposure to bleaching substances with pH values ranging between 5.2 and 5.8, which could initiate a descaling process involving the loss of minerals such as calcium [31].…”
Section: Discussionsupporting
confidence: 71%
“…Carbamide peroxide is unstable and breaks down immediately upon contact with tissue and saliva, first dissociating into hydrogen peroxide and urea and subsequently into oxygen, water, and carbon dioxide [4,8]. The apparent mechanism of action of bleaching agents on tooth structures is the oxidation of dentin molecules, which causes color changes [9]. This oxidation reaction can interfere with the structural integrity of restorative materials [10].…”
Section: Introductionmentioning
confidence: 99%
“…15 Furthermore, numerous studies have examined the efficacy of sodium ascorbate in removing oxygen radicals generated by bleaching gels from enamel and dentin. 37,38,57…”
Section: Resultsmentioning
confidence: 99%
“…Although the effects of the hydrocortisone are more potent if they are applied systematically, due to the potential unwanted reactios such way of application is not justified within the scope of teeth sensitivity when it comes to the whitening (29)(30)(31). Carvedilol was applied in the form of gel by which teeth are covered after the bleaching treatment (32)(33)(34)(35) The effect mechanism depends on type and group to which the drug belongs. Corticosteroids and glycocorticoids represent the group of drugs which possess extremey potent anti-inflammatory effect, and are chemically extremely liposoluble drugs, which as such can unhindered penetrate to the cell membrane and reach the cytoplasmosis, and even penetrate the cell nucleus.…”
Section: Perioperative Application Of the Anti-inflammatry Drugs In P...mentioning
confidence: 99%